Red mud-based shield synchronous grouting material and preparation method thereof
By using the excitation agent of red mud and slag combined with sodium water glass solution to prepare the synchronous grouting material with high strength and excellent durability, solve the problem of insufficient stability of traditional materials under complex geological conditions. The environmental protection performance of materials is improved and the construction efficiency is improved.
Patent Information
- Application Number
- CN202411534602.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-28
AI Technical Summary
The application of traditional single-fluid hard slurry in water-rich and high-pressure strata has problems such as insufficient stability, easy separation and stratification, and it is difficult to meet the tunnel construction needs under complex geological conditions.
Using red mud and slag dual mixtures as a gel material, combined with the use of sodium water glass solution as alkaline hair motor agent, by adjusting the proportion of red mud, the concentration of water glass, and the liquid solid ratio, it has high early intensity. , Clear mud -based shield in the late stage of improvement, excellent penetration and anti -soluble performance synchronous grouting materials.
It significantly improves the density and mechanical properties of the material, extended the service life of the shield tunnel structure, reduced the amount of cement, reduced carbon emissions, and was suitable for the simultaneous grouting operation of the shield tunnel rich in water -rich.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of synchronous grouting materials for shield tunnels, in particular to a red mud-based synchronous grouting material for shield tunnels and a preparation method thereof. Background Art
[0002] In shield tunnel construction, synchronous grouting is a key technology, which involves grouting the gap between the segments and the soil while the shield machine is excavating, aiming to reinforce the surrounding soil and protect the tunnel structure. Therefore, the shield synchronous grouting material must not only solve the problem of ground subsidence, but also ensure the durability of the tunnel structure. Single-liquid hard slurry is widely used as a synchronous grouting material due to its early and late strength, appropriate setting time and simple preparation process. However, this material has the problems of insufficient stability, easy segregation and stratification, which affects the filling effect, and its preparation is highly dependent on cement. In recent years, as shield tunnel projects continue to extend to complex geological conditions, such as water-rich strata, cross-river and cross-sea projects, and high-water-pressure strata, traditional single-liquid hard slurry faces severe challenges. The high water pressure and dissolution in these special strata put forward higher requirements on the performance of synchronous grouting materials, which are often difficult to meet with traditional synchronous grouting materials, resulting in increased risks in tunnel construction and worrying long-term safety performance.
[0003] Sintered red mud is made by high-temperature calcination of bauxite, coal powder, gypsum and other materials. It has a stable structure, rich calcium and aluminum elements, and has potential gelling activity. At the same time, its harmful substances and heavy metal content are low and stable, and its environmental impact is small. With the continuous maturity of alkali excitation technology, this technology can activate the gelling activity of red mud, opening up a new way for the application of red mud in synchronous grouting materials for shield tunnels. However, current research focuses on the basic physical and mechanical properties of shield synchronous grouting materials, and the discussion on its durability such as impermeability and corrosion resistance required as the primary protective layer in tunnel lining is still insufficient. These durability properties are crucial to ensure the long-term stable operation of tunnels under extreme geological conditions and are key indicators for evaluating the comprehensive performance of synchronous grouting materials. Therefore, the development of a new synchronous grouting material that can reduce cement consumption and carbon emissions, efficiently utilize a variety of industrial solid wastes, improve environmental protection performance, and can be stably applied under water-rich strata conditions under the premise of taking into account the basic indicators of synchronous grouting materials for shield tunnels has become a key issue to be solved in the field of synchronous grouting of shield tunnels in water-rich strata construction. Summary of the invention
[0004] The object of the present invention is to provide a red mud-based shield synchronous grouting material and a preparation method thereof, wherein the material selects a binary mixture of red mud and slag as a cementitious material, and combines a sodium water glass solution as an alkali activator. By adjusting the weight of the red mud, the concentration and modulus of the water glass solution, and the liquid-solid ratio, the grouting material exhibits high early strength, rapid improvement of late strength, a wide range of fluidity control, and excellent impermeability and corrosion resistance, thereby effectively extending the service life of the shield tunnel structure in water-rich strata, and by using a large amount of red mud, the amount of cement used is significantly reduced, and it can be widely used in the synchronous grouting operation of shield tunnels in water-rich strata.
[0005] The technical solution adopted by the present invention is: a red mud-based shield synchronous grouting material, the raw materials and weight proportions of which are:
[0006] 500-700 parts of red mud, which is sintered red mud, and its chemical components mainly include CaO and SiO2, and their content reaches more than 59% of the total mass;
[0007] 300-500 parts of slag, which is blast furnace slag, S95 grade blast furnace slag powder, with an apparent density of 3.10g / cm 3 , with a specific surface area of 429m 2 / kg;
[0008] The water glass solution is a sodium water glass solution, the modulus after preparation is 1.2-2.0, the concentration is 18%-27%, 700-900 parts;
[0009] 1538.46 parts of fine sand, which is ordinary fine river sand, with a fineness modulus of 1.86, a mud content of 1.68%, and a bulk density of 1528kg / m 3 ;
[0010] 5 parts of water reducer, which is a naphthalene-based water reducer;
[0011] 20 parts of retarder, which is barium nitrate;
[0012] Described sodium water glass solution is prepared as follows:
[0013] Weigh the required original water glass solution, add NaOH, adjust the molar ratio of SiO2 to Na2O according to formula (1), prepare a water glass solution with a modulus of 1.6, calculate the content of Na2O according to formula (2) to be 17.61%, and the amount of sodium oxide to be added is 9.07%. It is known that the relative molecular masses of Na2O and NaOH are 62 and 40 respectively. According to formula (3), the amount of NaOH to be added is calculated as 11.7% of the mass of the water glass solution to obtain a modulus of 1.6, and then add the water glass solution with the adjusted modulus into water to adjust its concentration. The concentration of the adjusted 1.6 modulus water glass is 40.2%. In order to adjust its concentration to 23%, it is necessary to add water according to 83.56% of the mass of the water glass solution, and so on, to achieve the concentration of the adjusted water glass solution.
[0014] Na2SiO3+2NaOH→Na2SiO3+Na2O+H2O(1)
[0015]
[0016] The original water glass solution has a modulus n of 3.3, a SiO2 content of 27.3%, and a Na2O content of 8.54%.
[0017] The added NaOH is solid sodium hydroxide with a purity of ≥96%, white granular appearance, and is easily soluble in water.
[0018] Furthermore, the raw materials and weight proportions of the red mud-based shield synchronous grouting material are as follows:
[0019] 600 parts of red mud, which is sintered red mud, and its chemical components mainly include CaO and SiO2, and their content reaches more than 59% of the total mass;
[0020] 400 parts of slag, which is blast furnace slag, S95 grade blast furnace slag powder, with an apparent density of 3.10 g / cm3 and a specific surface area of 429 m2 / kg;
[0021] The water glass solution is a sodium water glass solution, the modulus after preparation is 1.6, the concentration is 20%, 750 parts;
[0022] 1538.46 parts of fine sand, which is ordinary fine river sand, with a fineness modulus of 1.86, a mud content of 1.68%, and a bulk density of 1528kg / m3;
[0023] 5 parts of water reducer, which is a naphthalene-based water reducer;
[0024] 20 parts of retarder, which is barium nitrate;
[0025] Described sodium water glass solution is prepared as follows:
[0026] Weigh the required original water glass solution, add NaOH, adjust the molar ratio of SiO2 to Na2O according to formula (1), prepare a water glass solution with a modulus of 1.6, calculate the content of Na2O according to formula (2) to be 17.61%, and the amount of sodium oxide to be added is 9.07%. It is known that the relative molecular masses of Na2O and NaOH are 62 and 40 respectively. According to formula (3), the amount of NaOH to be added is calculated as 11.7% of the mass of the water glass solution to obtain a modulus of 1.6, and then add the water glass solution with the adjusted modulus into water to adjust its concentration. The concentration of the adjusted 1.6 modulus water glass is 40.2%. In order to adjust its concentration to 23%, it is necessary to add water according to 83.56% of the mass of the water glass solution, and so on, to achieve the concentration of the adjusted water glass solution, Na2SiO3+2NaOH→Na2SiO3+Na2O+H2O(1)
[0027]
[0028] The original water glass solution has a modulus n of 3.3, a SiO2 content of 27.3%, and a Na2O content of 8.54%.
[0029] The added NaOH is solid sodium hydroxide with a purity of ≥96%, white granular appearance, and is easily soluble in water.
[0030] The method for preparing the red mud-based shield synchronous grouting material comprises the following steps:
[0031] (1) Weighing required amounts of original water glass solution, NaOH and water, preparing a water glass solution with a modulus of 1.2-2.0 and a concentration of 18%-27%, and weighing 700-900 parts of a water glass solution with a modulus of 1.2-2.0 and a concentration of 18%-27% at a liquid-to-solid ratio of 0.7-0.9;
[0032] (2) Weigh 500-700 parts of red mud, 300-500 parts of slag, 1538.46 parts of fine sand, 5 parts of water reducer and 20 parts of retarder, put them into a blender and stir them at a low speed for 3 minutes until they are uniform, then add the water glass solution, and then stir the uniformly mixed powder and the water glass solution at a high speed for 4 minutes to obtain the red mud-based shield synchronous grouting material.
[0033] A red mud-based shield synchronous grouting material, the raw materials and weight proportions thereof are:
[0034] 500-700 parts of red mud, which is sintered red mud, and its chemical components mainly include CaO and SiO2, and their content reaches more than 59% of the total mass;
[0035] 300-500 parts of slag, which is blast furnace slag, S95 grade blast furnace slag powder, with an apparent density of 3.10g / cm 3 , with a specific surface area of 429m 2 / kg;
[0036] The water glass solution is a sodium water glass solution, the modulus after preparation is 1.2-2.0, the concentration is 18%-27%, 700-900 parts;
[0037] 1538.46 parts of fine sand, which is ordinary fine river sand, with a fineness modulus of 1.86, a mud content of 1.68%, and a bulk density of 1528kg / m 3 ;
[0038] 5 parts of water reducer, which is a naphthalene-based water reducer;
[0039] 20 parts of retarder, which is barium nitrate;
[0040] Described sodium water glass solution is prepared as follows:
[0041] Weigh the required original water glass solution, add NaOH, adjust the molar ratio of SiO2 to Na2O according to formula (1), prepare a water glass solution with a modulus of 1.6, calculate the content of Na2O according to formula (2) to be 17.61%, and the amount of sodium oxide to be added is 9.07%. It is known that the relative molecular masses of Na2O and NaOH are 62 and 40 respectively. According to formula (3), the amount of NaOH to be added is calculated as 11.7% of the mass of the water glass solution to obtain a modulus of 1.6, and then add the water glass solution with the adjusted modulus into water to adjust its concentration. The concentration of the adjusted 1.6 modulus water glass is 40.2%. In order to adjust its concentration to 23%, it is necessary to add water according to 83.56% of the mass of the water glass solution, and so on, to achieve the concentration of the adjusted water glass solution.
[0042] Na2SiO3+2NaOH→Na2SiO3+Na2O+H2O(1)
[0043]
[0044] The original water glass solution has a modulus n of 3.3, a SiO2 content of 27.3%, and a Na2O content of 8.54%. The manufacturer is Jiashan Yourui Refractory Material Co., Ltd.
[0045] The added NaOH is solid sodium hydroxide with a purity of ≥96%, white granular appearance, and is easily soluble in water.
[0046] The method for preparing the red mud-based shield synchronous grouting material comprises the following steps:
[0047] (1) Weighing required amounts of original water glass solution, NaOH and water, preparing a water glass solution with a modulus of 1.2-2.0 and a concentration of 18%-27%, and weighing 700-900 parts of a water glass solution with a modulus of 1.2-2.0 and a concentration of 18%-27% at a liquid-to-solid ratio of 0.7-0.9;
[0048] (2) Weigh 500-700 parts of red mud, 300-500 parts of slag, 1538.46 parts of fine sand, 5 parts of water reducer and 20 parts of retarder, put them into a blender and stir at low speed for 3 minutes until they are uniform. Then add the water glass solution, and then stir the uniformly mixed powder and the water glass solution at high speed for 4 minutes.
[0049] Through the above technical scheme, the influence of four factors, namely the proportion of red mud in cementitious powder, the concentration of water glass, modulus and liquid-solid ratio, on the slurry characteristics was deeply explored to determine the optimal levels of these four factors in shield grouting materials. On the premise of ensuring that the grouting materials meet the performance requirements of initial fluidity, water seepage rate, stone rate and setting time, while taking into account environmental protection and economy, the prepared grouting materials are significantly superior to traditional single-liquid hard slurries in mechanical properties, impermeability and corrosion resistance, and can be widely used in synchronous grouting operations of shield tunnels in water-rich strata.
[0050] Technical principle:
[0051] Red mud and slag, as industrial by-products, are rich in SiO2, Al2O3 and Fe2O3. They can react with alkaline activators (such as sodium water glass) under alkaline conditions to form aluminosilicate gel, becoming a viable alternative to traditional cementitious materials. Their fine particles can effectively fill the micropores in the grouting material, reduce the porosity, and thus enhance the material's impermeability and durability. In an alkaline environment, red mud and slag dissolve to release a large amount of Si and Al ions, which combine with OH- ions in the alkaline activator to further promote the formation of aluminosilicate gel and enhance the mechanical properties of the material. In addition, by adjusting the mixing ratio of red mud and slag, the setting time of the grouting material can be regulated to flexibly adapt to different construction needs.
[0052] The concentration and modulus of water glass have an important influence on the mechanical properties of red mud-based grouting materials. The increase in concentration can increase the supply of silicon sources, promote gel formation, refine the pore structure, and thus improve the density and strength of the material. The change in modulus affects the dissolution rate and gelation process of red mud and slag by adjusting the alkalinity of water glass. Using water glass with an appropriate low modulus can accelerate the reaction, form a uniform and tough gel network, and improve the early strength of the material; while high modulus water glass helps to build a more uniform and stronger gel structure and optimize the long-term mechanical properties of the material.
[0053] Liquid-to-solid ratio, as the ratio parameter of liquid to solid raw materials in grouting materials, has a significant impact on the mechanical properties of slurry. A reasonable liquid-to-solid ratio can ensure the uniform formation of gel network and improve the density and strength of the material. Too high or too low liquid-to-solid ratio will interfere with the formation and distribution of gel, thereby affecting the porosity and durability of the material. A low liquid-to-solid ratio may shorten the setting time but increase the volume shrinkage, while a high liquid-to-solid ratio may prolong the setting time and reduce the strength of the material.
[0054] The beneficial effects of the present invention are:
[0055] 1. Compared with traditional shield synchronous grouting materials, red mud-based shield synchronous grouting materials have significantly improved environmental friendliness. By simultaneously utilizing industrial by-products red mud and slag, it reduces the use of cement, reduces carbon emissions, and realizes the resource utilization of waste.
[0056] 2. The geopolymer gel generated by the alkali-induced reaction of this material effectively improves the density and mechanical properties, meets the standards of synchronous grouting materials for shield tunnels, and exhibits excellent anti-seepage and anti-corrosion properties, enhances durability and extends the service life of the project. It is suitable for synchronous grouting operations in shield tunnels in water-rich strata.
[0057] 3. By finely controlling the red mud dosage, the concentration and modulus of the water glass solution, and the liquid-to-solid ratio, the red mud-based shield synchronous grouting material can optimize construction performance, reduce costs, and improve construction efficiency. At the same time, it shows better adaptability and stability in complex underground environments, providing a reliable, economical, and environmentally friendly new solution for shield tunnel construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 Schematic diagram of the effect of red mud dosage on fluidity.
[0059] Figure 2 Schematic diagram of the effect of red mud dosage on water seepage rate.
[0060] Figure 3 Schematic diagram of the effect of red mud dosage on stone rate.
[0061] Figure 4 Schematic diagram of the effect of red mud dosage on setting time.
[0062] Figure 5 Schematic diagram of the effect of red mud dosage on compressive strength.
[0063] Figure 6 Schematic diagram of the effect of red mud content on flexural strength.
[0064] Figure 7 Schematic diagram of red mud dosage and mass loss rate.
[0065] Figure 8Schematic diagram of the effect of red mud dosage on compressive strength after dissolution.
[0066] Fig. 9 Schematic diagram of the effect of red mud dosage on flexural strength after dissolution.
[0067] Fig.10 Schematic diagram of the effect of red mud dosage on anti-seepage pressure.
[0068] Fig.11 Schematic diagram of the effect of water glass modulus on fluidity.
[0069] Fig.12 Schematic diagram of the effect of water glass modulus on water bleeding rate.
[0070] Fig.13 Schematic diagram of the effect of water glass modulus on stone rate.
[0071] Fig.14 Schematic diagram of the effect of water glass modulus on setting time.
[0072] Fig.15 Schematic diagram of the effect of water glass modulus on compressive strength.
[0073] Fig.16 Schematic diagram of the effect of water glass modulus on flexural strength.
[0074] Fig.17 Schematic diagram of water glass modulus versus mass loss rate.
[0075] Fig.18 Schematic diagram of the effect of water glass modulus on compressive strength after dissolution.
[0076] Fig.19 Schematic diagram of the effect of water glass modulus on flexural strength after dissolution.
[0077] Fig. 20 Schematic diagram of the effect of water glass modulus on anti-seepage pressure.
[0078] Fig.21 Schematic diagram of the effect of water glass concentration on fluidity.
[0079] Fig. 22 Schematic diagram of the effect of water glass concentration on water bleeding rate.
[0080] Fig.23 Schematic diagram of the effect of water glass concentration on stone formation rate.
[0081] Fig.24 Schematic diagram of the effect of water glass concentration on setting time.
[0082] Fig.25 Schematic diagram of the effect of water glass concentration on compressive strength.
[0083] Fig.26Schematic diagram of the effect of water glass concentration on flexural strength.
[0084] Fig. 27 Schematic diagram of water glass concentration and mass loss rate.
[0085] Fig.28 Schematic diagram of the effect of water glass concentration on the compressive strength after dissolution.
[0086] Fig.29 Schematic diagram of the effect of water glass concentration on the flexural strength after dissolution.
[0087] Fig.30 Schematic diagram of the effect of water glass concentration on osmotic pressure.
[0088] Fig.31 Schematic diagram of the effect of liquid-to-solid ratio on fluidity.
[0089] Fig.32 Schematic diagram of the effect of liquid-to-solid ratio on water seepage rate.
[0090] Fig.33 Schematic diagram of the effect of liquid-to-solid ratio on stone formation rate.
[0091] Fig.34 Schematic diagram of the effect of liquid-to-solid ratio on setting time.
[0092] Fig.35 Schematic diagram of the effect of liquid-to-solid ratio on compressive strength.
[0093] Fig.36 Schematic diagram of the effect of liquid-to-solid ratio on flexural strength.
[0094] Fig.37 Schematic diagram of liquid-to-solid ratio versus mass loss rate.
[0095] Fig.38 Schematic diagram of the effect of liquid-to-solid ratio on compressive strength after dissolution.
[0096] Fig.39 Schematic diagram of the effect of liquid-to-solid ratio on flexural strength after dissolution.
[0097] Fig.40 Schematic diagram of the effect of liquid-to-solid ratio on osmotic pressure. DETAILED DESCRIPTION
[0098] The technical solution of the present invention is further described in detail below in conjunction with embodiments.
[0099] Example 1
[0100] The red mud-based shield synchronous grouting material of the present invention has the following raw material composition:
[0101] Red mud: The chemical composition of sintered red mud mainly includes CaO and SiO2, and its content reaches more than 59% of the total mass. The manufacturer is Henan Zhengzhou Huifeng New Materials Co., Ltd.;
[0102] Slag: S95 grade slag, produced by Gongyi Longze Water Purification Materials Co., Ltd.;
[0103] Original water glass solution: modulus n is 3.3, SiO2 content is 27.3%, Na2O content is 8.54%, produced by Jiashan Yourui Refractory Material Co., Ltd.;
[0104] Sodium hydroxide: solid sodium hydroxide, purity ≥96%;
[0105] Sand: Ordinary fine river sand, fineness modulus is 1.86, mud content is 1.68%, bulk density is 1528kg / m 3 ;
[0106] Retarder: barium nitrate;
[0107] Water reducer: naphthalene-based water reducer.
[0108] The chemical compositions of the red mud and slag selected above are shown in Table 1.
[0109] Table 1 Chemical composition of sintering red mud and slag (%)
[0110]
[0111] The specific performance indicators of the original water glass solution selected above are shown in Table 2.
[0112] Table 2 Performance indicators of original water glass solution
[0113]
[0114] Since the modulus and concentration range of the water glass solution required in the present invention are 1.2-2.0 and 18%-27% respectively, sodium hydroxide and water need to be added to the original water glass solution, and the steps are as follows:
[0115] Weigh the required original water glass solution, add NaOH, adjust the molar ratio of SiO2 to Na2O according to formula (1), prepare a water glass solution with a modulus of 1.6, calculate the content of Na2O according to formula (2) to be 17.61%, and the amount of sodium oxide to be added is 9.07%. It is known that the relative molecular masses of Na2O and NaOH are 62 and 40 respectively. According to formula (3), the amount of NaOH to be added is calculated as 11.7% of the mass of the water glass solution to obtain a modulus of 1.6, and then add the water glass solution with the adjusted modulus into water to adjust its concentration. The concentration of the adjusted 1.6 modulus water glass is 40.2%. In order to adjust its concentration to 23%, it is necessary to add water according to 83.56% of the mass of the water glass solution, and so on, to achieve the concentration of the adjusted water glass solution.
[0116] Na2SiO3+2NaOH→Na2SiO3+Na2O+H2O(1)
[0117]
[0118] Example 2
[0119] This embodiment is an example of a method for preparing the red mud-based shield synchronous grouting material of the present invention, and its raw materials and dosage ratio are shown in Table 3, comprising the following steps:
[0120] (1) Weigh the required amounts of original water glass solution, NaOH and water, adjust the water glass concentration and modulus according to Example 1, and weigh the water glass solution according to the liquid-to-solid ratio.
[0121] (2) Weigh red mud, slag, fine sand, water reducer and retarder, put them into a blender and stir at low speed for 3 minutes until they are uniform. Then add water glass solution, and stir the uniformly mixed powder and water glass solution at high speed for 4 minutes.
[0122] Table 3 Slurry ratio of Examples 2-18
[0123]
[0124] Example 3
[0125] This embodiment is the third example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0126] The difference between this embodiment and embodiment 2 is that 700 parts of red mud and 300 parts of slag are used, and the remaining steps and amounts are the same as those in embodiment 2.
[0127] Example 4
[0128] This embodiment is the fourth example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0129] The difference between this embodiment and embodiment 2 is that 650 parts of red mud and 350 parts of slag are used, and the remaining steps and amounts are the same as those in embodiment 2.
[0130] Example 5
[0131] This embodiment is the fifth example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, and comprises the following steps:
[0132] The difference between this embodiment and embodiment 2 is that the red mud accounts for 550 parts of the cementitious powder and the slag accounts for 450 parts, and the remaining steps and amounts are the same as those in embodiment 2.
[0133] Example 6
[0134] This embodiment is the sixth example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0135] The difference between this embodiment and embodiment 2 is that 500 parts of red mud and 500 parts of slag are used, and the remaining steps and amounts are the same as those in embodiment 2.
[0136] Example 7
[0137] This embodiment is the seventh example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0138] The difference between this embodiment and embodiment 2 is that the modulus of water glass is 1.2, and the remaining steps and amounts are the same as those in embodiment 2.
[0139] Example 8
[0140] This embodiment is the eighth example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0141] The difference between this embodiment and embodiment 2 is that the modulus of water glass is 1.4, and the remaining steps and amounts are the same as those in embodiment 2.
[0142] Example 9
[0143] This embodiment is the ninth example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, and comprises the following steps:
[0144] The difference between this embodiment and embodiment 2 is that the modulus of water glass is 1.8, and the remaining steps and amounts are the same as those in embodiment 2.
[0145] Example 10
[0146] This embodiment is the tenth example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0147] The difference between this embodiment and embodiment 2 is that the water glass modulus is 2.0, and the remaining steps and amounts are the same as those in embodiment 2.
[0148] Embodiment 11
[0149] This embodiment is the 11th example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0150] The difference between this embodiment and embodiment 2 is that the concentration of water glass is 18%, and the remaining steps and amounts are the same as those in embodiment 2.
[0151] Example 12
[0152] This embodiment is the 12th example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0153] The difference between this embodiment and embodiment 2 is that the concentration of water glass is 20%, and the remaining steps and amounts are the same as those in embodiment 2.
[0154] Example 13
[0155] This embodiment is the 13th example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, and comprises the following steps:
[0156] The difference between this embodiment and embodiment 2 is that the concentration of water glass is 25%, and the remaining steps and amounts are the same as those in embodiment 2.
[0157] Embodiment 14
[0158] This embodiment is the 14th example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0159] The difference between this embodiment and embodiment 2 is that the concentration of water glass is 27%, and the remaining steps and amounts are the same as those in embodiment 2.
[0160] Embodiment 15
[0161] This embodiment is the 15th example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0162] The difference between this embodiment and embodiment 2 is that the liquid-to-solid ratio is 0.7, 700 parts of water glass are used, and the remaining steps and amounts are the same as those in embodiment 2.
[0163] Example 16
[0164] This embodiment is the 16th example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0165] The difference between this embodiment and embodiment 2 is that the liquid-to-solid ratio is 0.80, the amount of water glass is 800 parts, and the remaining steps and amounts are the same as those in embodiment 2.
[0166] Embodiment 17
[0167] This embodiment is the 17th example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0168] The difference between this embodiment and embodiment 2 is that the liquid-to-solid ratio is 0.85, the amount of water glass is 850 parts, and the remaining steps and amounts are the same as those in embodiment 2.
[0169] Embodiment 18
[0170] This embodiment is the 18th example of the method for preparing the red mud-based shield synchronous grouting material according to the present invention, comprising the following steps:
[0171] The difference between this embodiment and embodiment 2 is that the liquid-to-solid ratio is 0.9, the amount of water glass is 900 parts, and the remaining steps and amounts are the same as those in embodiment 2.
[0172] Performance testing
[0173] Detection method / test method
[0174] The material was prepared according to the preparation method of red mud-based shield synchronous grouting material in Example 1-17, and then tested according to the following test method. The test results are shown in Table 4.
[0175] Fluidity: Refer to GB / T 50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials".
[0176] Water seepage rate: refer to T / CECS 563-2018 "Technical Specifications for Application of Synchronous Grouting Materials in Shield Tunnels".
[0177] Stone rate: refer to T / CECS 563-2018 "Technical Code for Application of Synchronous Grouting Materials in Shield Tunnels".
[0178] Setting time: refer to JGJ / T70-2009 "Standard for Test Methods for Basic Properties of Building Mortar", and use ZKS-100 Mortar Setting Time Meter for measurement.
[0179] Compression and flexural strength: Refer to (GB / T17671-1999) "Test method for strength of cement mortar (ISO method)" for strength standard testing, and conduct compression and flexural mechanical performance analysis on specimens with a size of 40mm×40mm×160mm. Use YAW-300 / 10 cement compression and flexural integrated machine to complete relevant tests to test its mechanical properties.
[0180] Seepage resistance: Referring to the provisions of JGJ / T70-2009 "Standard for Test Methods of Basic Properties of Building Mortar" and JC474-2008 "Mortar and Concrete Waterproof Agent", the seepage resistance performance of red mud-based synchronous grouting materials was tested. The test was conducted using a test mold with an upper diameter of 70mm, a lower diameter of 80mm, and a height of 30mm, and using an SS-15 mortar seepage resistance tester.
[0181] Anti-corrosion performance test method: Saturated ammonium chloride (NH4Cl) solution is used as the dissolution medium and prepared at room temperature (25°C). The pH value of the solution is about 5.6, which is acidic. Since ammonium chloride has high water solubility, ammonium chloride crystals need to be added gradually and stirred continuously during preparation until the solution is saturated and NH4Cl is excessive. The grouting material is made into a standard test block, and after curing for a specified time, the anti-corrosion performance test is carried out. The test block is immersed in a saturated ammonium chloride solution, and the solution is monitored and replaced regularly during the period to maintain its stability. After the test, the surface of the test block is cleaned, dried to constant weight, and then the mass after dissolution is weighed. The mass loss rate is calculated by comparing the initial mass and the mass after dissolution. In addition, the compressive and flexural strength tests were also carried out on the test blocks before and after dissolution to evaluate the effect of dissolution on the strength properties of the material.
[0182] Table 4 Test results of Examples 2-18
[0183]
[0184] Table 5 Test results of anti-seepage performance of examples 2, 3, 4, 5, 8, 9, 12, 13 and 16
[0185]
[0186]
[0187] Table 6 Performance test results after dissolution of Examples 2-18
[0188]
[0189] It can be seen from the test data of the single factor test of Examples 2-18 that the red mud dosage, water glass modulus, concentration and liquid-to-solid ratio have different degrees of influence on the slurry fluidity, water seepage rate, stone rate, setting time, compressive and flexural strength, impermeability and anti-corrosion properties.
[0190] High red mud content and high modulus water glass will reduce the fluidity of red mud-based grouting material slurry. Water glass concentration and liquid-solid ratio have a promoting effect on the fluidity of the slurry. As the red mud content increases from 500 to 700 parts, the fluidity of the geopolymer grouting slurry decreases by 16%. As the water glass modulus increases from 1.2 to 2.0, the fluidity decreases by 20%. When the water glass concentration increases from 18% to 27%, the fluidity increases by 38%. The liquid-solid ratio increases from 0.7 to 0.9, and the fluidity increases by 40%.
[0191] The water seepage rate of the slurry is closely related to the stone formation rate. The higher the water seepage rate of the slurry, the greater the shrinkage of the stone body after hardening and the lower the stone formation rate. When the red mud content increases from 500 parts to 700 parts, the water seepage rate of the slurry decreases from 1.30% to 0.30%, and the corresponding stone formation rate increases from 98.7% to 99.7%. Increasing the red mud content is beneficial to improving the stability of the slurry. When the water glass modulus increases from 1.2 to 2.0, the water seepage rate of the slurry increases from 0 to 1.5%, and the stone formation rate decreases from 100% to 98.5%. Low modulus water glass is beneficial to the stability of the slurry. When the water glass concentration increases from 18% to 27%, the water seepage rate of the slurry decreases from 1.60% to 0, and the stone formation rate increases from 98.40% to 100%. Increasing the water glass concentration is beneficial to promoting the stability of the slurry. As the liquid-to-solid ratio increased from 0.7 to 0.9, the water seepage rate of the slurry increased from 0 to 2.3%, and the stone rate decreased from 100% to 97.7%.
[0192] When the red mud content increased from 500 to 700 parts, the slurry setting time increased from 108 minutes to 287 minutes, an increase of 167%; the low modulus (1.2) activator solution shortened the slurry setting time (to 122.5 minutes), while the high modulus (2.0) activator solution prolonged the slurry setting time (to 232.5 minutes), with an increase of 89.8%. When the concentration of water glass solution in the alkali activator increased from 18% to 27%, the slurry setting time was shortened from 360 minutes to 75 minutes, a decrease of 79.1%.
[0193] As the red mud content increases from 500 to 700 parts, the water permeability depth increases from 13.7 mm to 30 mm (completely permeable). As the water glass modulus increases from 1.2 to 2.0, the impermeability of the stone body shows a trend of first increasing and then decreasing. Both too low water glass modulus and too high water glass modulus have an adverse effect on the impermeability of the stone body. As the water glass concentration increases from 18% to 27%, the impermeability of the stone body gradually increases. As the liquid-solid ratio increases, the impermeability of the stone body gradually decreases. When the liquid-solid ratio increases from 0.7 to 0.9, the water permeability pressure of the stone body decreases rapidly.
[0194] The increase of red mud content will cause the compressive strength of the slurry stone to decrease. The increase of the modulus of the alkali activator will cause the compressive strength of the stone to increase first and then decrease. When the concentration of water glass increases to 25%, the compressive strength of the stone gradually increases in both the early and late stages, but when the concentration is higher than 25%, the early strength will decrease instead. The increase of liquid-solid ratio will cause the early compressive strength of the stone to increase first and then decrease, and gradually decrease in the later stage.
[0195] Increasing the amount of red mud will have a positive effect on the flexural strength of the slurry stone, especially in the early stages. Low modulus water glass solution will cause the stone to produce a large amount of gel, but too high a concentration will also lead to an increase in pores and microcracks, affecting the flexural strength of the stone. When the water glass concentration reaches 23%, the flexural strength of the stone reaches the optimal value. With the increase of liquid-solid ratio, the flexural strength of the stone gradually decreases. A high liquid-solid ratio will lead to a decrease in the production of aluminosilicate gel and an increase in pores and cracks inside the stone, thereby affecting the flexural strength of the stone.
[0196] With the extension of dissolution time, the mass loss of the stone body increased under all test conditions. Increasing the red mud content and water glass modulus can reduce the mass loss, while increasing the water glass concentration and liquid-solid ratio will lead to an increase in the mass loss rate. Compared with traditional cement-based synchronous grouting materials, red mud-based synchronous grouting materials have better quality stability in water-rich environments, which is attributed to the stability of its internal zeolite-like structured aluminosilicate gel material.
[0197] As the soaking time increases, the compressive strength of the stone body decreases. The increase in the amount of red mud will cause the compressive strength loss of the stone body to increase first and then decrease. As the dissolution reaction proceeds, the filling effect of red mud particles becomes apparent. Excessive red mud content will lead to the loss of cementitious materials, thereby increasing the compressive strength loss in the later stage of dissolution; as the modulus of water glass increases, the compressive strength loss of the stone body increases. As the modulus increases, the alkalinity of the alkali activator decreases, and the degree of polymerization of the internal gel product decreases. The combined effect of the two increases the compressive strength loss of the stone body after dissolution; as the concentration of water glass increases, excessive water glass will become the first line of defense to resist dissolution, and ultimately reduce the compressive strength loss of the stone body; the increase in liquid-solid ratio will increase the compressive strength loss of the stone body, and more free water will cause the pore structure of the material to loosen, making the solution easier to erode. Compared with traditional cement-based materials, red mud-based synchronous grouting materials have less mass loss after dissolution and higher foundation strength, which can improve the safety, stability and service life of the tunnel and reduce the cost of later maintenance.
[0198] In summary, the present invention provides a red mud-based synchronous grouting material using industrial waste red mud and slag as main raw materials. By controlling the red mud dosage, water glass concentration, modulus and liquid-solid ratio, the setting time, mechanical properties and durability of the material are optimized, so that it has significant application advantages in the field of synchronous grouting of shield tunnels in water-rich strata. The description of these technical solutions is intended to explain the core concepts and implementation methods of the present invention, rather than to limit the invention. For ordinary technicians in this technical field, according to the overall concept of the present invention, equal modifications, improvements or substitutions made to the above technical solutions should be deemed to be within the scope of protection of the present invention as long as they do not deviate from the basic ideas and creative features of the present invention.
Claims
1. A red mud-based shield synchronous grouting material, characterized in that: Its raw materials and weight parts are: 500-700 parts of red mud, which is sintered red mud, and its chemical components mainly include CaO and SiO2, and their content reaches more than 59% of the total mass; 300-500 parts of slag, which is blast furnace slag, S95 grade blast furnace slag powder, with an apparent density of 3.10g / cm 3 , with a specific surface area of 429m 2 / kg; The water glass solution is a sodium water glass solution, the modulus after preparation is 1.2-2.0, the concentration is 18%-27%, 700-900 parts; 1538.46 parts of fine sand, which is ordinary fine river sand, with a fineness modulus of 1.86, a mud content of 1.68%, and a bulk density of 1528kg / m 3 ; 5 parts of water reducer, which is a naphthalene-based water reducer; 20 parts of retarder, which is barium nitrate; Described sodium water glass solution is prepared as follows: Weigh the required original water glass solution, add NaOH, adjust the molar ratio of SiO2 to Na2O according to formula (1), prepare a water glass solution with a modulus of 1.6, calculate the content of Na2O according to formula (2) to be 17.61%, and the amount of sodium oxide to be added is 9.07%. It is known that the relative molecular masses of Na2O and NaOH are 62 and 40 respectively. According to formula (3), the amount of NaOH to be added is calculated as 11.7% of the mass of the water glass solution to obtain a modulus of 1.6, and then add the water glass solution with the adjusted modulus into water to adjust its concentration. The concentration of the adjusted 1.6 modulus water glass is 40.2%. In order to adjust its concentration to 23%, it is necessary to add water according to 83.56% of the mass of the water glass solution, and so on, to achieve the concentration of the adjusted water glass solution. Na2SiO3+2NaOH→Na2SiO3+Na2O+H2O(1) The original water glass solution has a modulus n of 3.3, a SiO2 content of 27.3%, and a Na2O content of 8.54%. The added NaOH is solid sodium hydroxide with a purity of ≥96%, white granular appearance, and is easily soluble in water.
2. The red mud-based shield synchronous grouting material according to claim 1, characterized in that: Its raw materials and weight parts are: 600 parts of red mud, which is sintered red mud, and its chemical components mainly include CaO and SiO2, and their content reaches more than 59% of the total mass; 400 parts of slag, which is blast furnace slag, S95 grade blast furnace slag powder, with an apparent density of 3.10 g / cm3 and a specific surface area of 429 m2 / kg; The water glass solution is a sodium water glass solution, the modulus after preparation is 1.6, the concentration is 20%, 750 parts; 1538.46 parts of fine sand, which is ordinary fine river sand, with a fineness modulus of 1.86, a mud content of 1.68%, and a bulk density of 1528kg / m3; 5 parts of water reducer, which is a naphthalene-based water reducer; 20 parts of retarder, which is barium nitrate; Described sodium water glass solution is prepared as follows: Weigh the required original water glass solution, add NaOH, adjust the molar ratio of SiO2 to Na2O according to formula (1), prepare a water glass solution with a modulus of 1.6, calculate the content of Na2O according to formula (2) to be 17.61%, and the amount of sodium oxide to be added is 9.07%. It is known that the relative molecular masses of Na2O and NaOH are 62 and 40 respectively. According to formula (3), the amount of NaOH to be added is calculated as 11.7% of the mass of the water glass solution to obtain a modulus of 1.6, and then add the water glass solution with the adjusted modulus into water to adjust its concentration. The concentration of the adjusted 1.6 modulus water glass is 40.2%. In order to adjust its concentration to 23%, it is necessary to add water according to 83.56% of the mass of the water glass solution, and so on, to achieve the concentration of the adjusted water glass solution. Na2SiO3+2NaOH→Na2SiO3+Na2O+H2O(1) The original water glass solution has a modulus n of 3.3, a SiO2 content of 27.3%, and a Na2O content of 8.54%. The added NaOH is solid sodium hydroxide with a purity of ≥96%, white granular appearance, and is easily soluble in water.
3. The method for preparing the red mud-based shield synchronous grouting material according to claim 1, characterized in that: The following steps are involved: (1) Weighing required amounts of original water glass solution, NaOH and water, preparing a water glass solution with a modulus of 1.2-2.0 and a concentration of 18%-27%, and weighing 700-900 parts of a water glass solution with a modulus of 1.2-2.0 and a concentration of 18%-27% at a liquid-to-solid ratio of 0.7-0.9; (2) Weigh 500-700 parts of red mud, 300-500 parts of slag, 1538.46 parts of fine sand, 5 parts of water reducer and 20 parts of retarder, put them into a blender and stir them at a low speed for 3 minutes until they are uniform, then add the water glass solution, and then stir the uniformly mixed powder and the water glass solution at a high speed for 4 minutes to obtain the red mud-based shield synchronous grouting material.
Citation Information
Cited By
Ecological grouting material based on shield muck and fiber modification and performance evaluation method
CN119954447A
Preparation method of green high-performance industrial solid waste-based grouting material
CN121159199A
Preparation method of green high-performance industrial solid waste-based grouting material
CN121159199B